EFEKTIVITAS PENGGUNAAN DANA BANTUAN OPERASIONAL SEKOLAH PADA MADRASAH IBTIDAIYAH SWASTA DI KABUPATEN PIDIE - Muhammad Andi; Murniati AR; Nasir Usman (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2015)
Abstract: The School Operational Assistance (BOS)program as one of the indicators of the completion of compulsory education program started from elementary school until senior high school/equal does not only aim to maintain the Gross Participation Rate but also to contribute important roles in improving the quality of education. The education fee is an important component in the implementation of education. The education process cannot run smoothly without financial support. The purpose of this study was to describe and analyze the matters related to the program of using the BOS funds, the strategy of usingthe BOS funds, and the supervision of the use ofBOS funds at Private Islamic Elementary Schools of Pidie Regency. The method used in this study was descriptive method with qualitative approach. The techniques of data collection used were interview, observation, and documentation. The subjects of this study were school principals, teachers, school treasures, and school committees. The result of this study showed that: (1) The program of using BOS funds at Private Islamic Elementary Schools of Pidie Regency was designed and implemented by the school principals with involving the school treasures, the senior teachers, and the school committees. The centralistic and de-centralistic system was adopted in Islamic elementary school financial system. (2) The strategy of using BOSat Private Islamic Elementary Schools of Pidie Regency in term of financial point was that all kind of expenditures for educational activity at school should be transparent for both the school principal and other school internals that are involved in the drafting process of School Budget.(3) The supervision of the use of BOS funds at Private Islamic Elementary Schools of Pidie Regency was carried out by the school principals and the officials of Regional Office of Religious Affairs of Pidie Regency as the internal supervisor. The supervision system was carried out through observing each income and expenditure of BOS funds. The audit by implementing indirect observation process, such as the expenditure, should be approved by the school principals or school treasures. The financial auditing was also carried out through auditing the financial statement of each activities, which were submitted by teachers or school treasures.Keywords: Effectiveness, School Operational Assistance Funds, and Private Islamic Elementary SchoolsAbstrak: Program BOS sebagai salah satu indikator penuntasan program wajib belajar sejak SD sampai SMA/sederajat, bukan hanya bertujuan mempertahankan Angka Partisipasi Kasar (APK), namun juga berkontribusi penting untuk peningkatan mutu pendidikan. Biaya pendidikan adalah komponen yang sangat penting dalam penyelenggaraan pendidikan. Proses pendidikan tidak dapat berjalan tanpa dukungan biaya. Tujuan penelitian ini untuk mendeskripsi dan menganalisis hal-hal yang berkenaan dengan: program penggunaan dana BOS, strategi penggunaan dana BOS, dan pengawasan penggunaan dana BOS pada Madrasah Ibtidaiyah Swasta di Kabupaten Pidie. Metode yang digunakan dalam penelitian ini adalah deskriptif dengan pendekatan kualitatif. Teknik pengumpulan data yang digunakan adalah wawancara, observasi, dan dokumentasi. Subjek penelitian: kepala sekolah, guru, bendaharawan sekolah, dan komite sekolah. Hasil penelitian menunjukkan bahwa: (1) Program penggunaan dana BOS pada Madrasah Ibtidaiyah Swasta di Kabupaten Pidie disusun dan dilaksanakan oleh kepala sekolah, dengan melibatkan bendaharawan, guru senior, dan komite sekolah. Pembiayaan pada madrasah ibtidaiyah menganut sistem sentralistik dan desentralistik; (2) Strategi penggunaan dana BOS pada Madrasah Ibtidaiyah Swasta di Kabupaten Pidie ditinjau dari sisi keuangan, bahwa semua jenis pengeluaran untuk kegiatan pendidikan pada sekolah harus diketahui bersama, baik kepala sekolah maupun pihak-pihak internal sekolah yang terlibat dalam proses penyusunan RAPBS; dan (3) Pengawasan penggunaan dana BOS pada madrasah ibtidaiyah swasta di Kabupaten Pidie dilakukan oleh kepala sekolah dan pejabat dari Kantor Kementerian Agama Kabupaten Pidie sebagai pengawas internal. Sistem pengawasan yang dilakukan adalah dengan cara mengamati setiap pemasukan dan pengeluaran dana BOS. Pemantauan atau pemeriksaan dengan melakukan pengamatan secara tidak langsung misalnya setiap pengeluaran dana harus atas persetujuan kepala sekolah atau bendaharawan. Pemeriksaan keuangan juga dilakukan dengan cara memeriksa laporan keuangan pada setiap kegiatan yang dilakukan, yang diserahkan oleh guru atau bendaharawan.Kata kunci: Efektivitas, Dana BOS, dan MIS